Study of Correlation Between Selected Financial Components (EBIT, Dividends, Retained Earnings, and Debt to Equity Ratio) with Stock Prices of Companies in Indonesian Real Estate Industry - Raden Aswin Rahadi; Harris Kristianto Yondi; Alexius Reinaldo Hartadi Budiman (JAF (Journal of Accounting and Finance), 2019)
The real estate industry in Indonesia is forecasted to keep growing in the future. There will be significant opportunities in the capital market for investment. It is essential for investors who will invest in this industry to understand what factors are essential to predict stocks price movement, especially for stock trading investors. For companies in the industry, knowing what they should do to attain growth more significant than the industry itself is essential to attract investors. The research purposes are to study the correlation between selected financial components and stock price. The analysis was done by calculating the correlation between financial components with stock price using 10-years period data. The results show there are six classes of companies according to correlation analysis: significant with EBIT, significant with dividend, significant with RE, significant with DER, multi significant, and insignificant. The most substantial component is the debt to equity ratio. Recommendation for investors is to understand the industry and aware of companies' activities before investing. Investing in sustainable companies leads to stable capital gain while for risk-taker investors, investing in other companies should be based on the projects handled by the company. For companies, they should have focused on the factors that correlate with their stock price.